Viscosity solutions to the ∞-Laplace equation in Grushin-type spaces - Thomas Bieske; Zachary Forrest (Modern Mathematical Methods)
In this paper, we prove the existence and uniqueness of viscosity solutions to the infinite Laplace equation in Grushin-type spaces whose tangent spaces consist of arbitrary triangular vector fields.